Tracing Ocean Circulation and Mixing From the Arctic to the Subpolar North Atlantic Using the 129I–236U Dual Tracer - Dale, Duncan; id_orcid:0 000-0002-3258-582X; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Vockenhuber, Christof; Macrander, Andreas; Ólafsdóttir, Sólveig; Middag, Rob; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655 (American Geophysical Union, 2024)
This study represents the first use of the artificial radionuclides 129I and 236U, released into the ocean mainly from Nuclear Reprocessing Plants, as a dual tracer in the vicinity of Iceland with novel estimation of ocean circulatory pathways and mixing in the region. Iceland lies at the gateway to the Arctic where warm, saline Atlantic waters interact with waters of Arctic origin in ways that have critical consequences for the strength and stability of the Atlantic Meridional Overturning Circulation. Many of these interactions are not yet fully understood, such as how Atlantic water circulates around the Arctic Ocean and Nordic Seas and the composition and fate of the major overflows of the Greenland-Scotland Ridge. Using new and previous measurements of 129I and 236U in seawater, we present a new method of appraising water mass provenance and mixing in the form of the 129I–236U dual mixing plot. With this method, we estimate that at least half the Atlantic-origin water entering the Arctic Ocean circulates around the Canada Basin before exiting at Fram Strait and that this outflow is increased by about 40% by mixing with Return Atlantic Water “short-circuiting” the Arctic Ocean at Fram Strait. We present tracer-based evidence that water carried by the East Greenland Current has an unbroken pathway to the Faroe-Shetland Channel and that Iceland-Scotland Overflow Water (ISOW) entrains 60% Labrador Sea Water during transit past southeast Iceland. We present an unambiguous way to differentiate ISOW from DSOW after they partially merge in the Irminger Sea. ISSN:0148-0227 ISSN:2169-9275